2019
DOI: 10.1038/s41598-019-48658-4
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake influences gut microbiota development of healthy Australian children from the age of one to two years

Abstract: Early life nutrition is a vital determinant of an individual’s life-long health and also directly influences the ecological and functional development of the gut microbiota. However, there are limited longitudinal studies examining the effect of diet on the gut microbiota development in early childhood. Here, up to seven stool samples were collected from each of 48 healthy children during their second year of life, and microbiota dynamics were assessed using 16S rRNA gene amplicon sequencing. Children’s dietar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 75 publications
2
26
0
2
Order By: Relevance
“…The B. breve strain M-16V colonizing the breastfed infant gut is regarded as safety [ 111 ], and exerts anti-inflammatory effects on allergic diseases after a single supplementation [ 111 , 112 ], or in combination with B. infantis M-63 and B longum BB536 [ 113 ], including both prenatal and postnatal periods [ 114 ].The probiotic B. breve strain M-16V and galacto/fructo-oligosaccharide (GOS/FOS) prebiotic mixture supplemented with fortified milk increase the relative abundances of Bifidobacterium spp. [ 115 ]. Probiotic supplementation with B. breve in preterm infants increases the production of serum transforming growth factor (TGF-β) levels, and enhances the deca-pentaplegic homolog3 (Smad3) mRNA expression for TGF-A signaling molecules [ 116 ].…”
Section: Short-chain Fatty Acids: a Link Between Maternal Vlckd Tmentioning
confidence: 99%
“…The B. breve strain M-16V colonizing the breastfed infant gut is regarded as safety [ 111 ], and exerts anti-inflammatory effects on allergic diseases after a single supplementation [ 111 , 112 ], or in combination with B. infantis M-63 and B longum BB536 [ 113 ], including both prenatal and postnatal periods [ 114 ].The probiotic B. breve strain M-16V and galacto/fructo-oligosaccharide (GOS/FOS) prebiotic mixture supplemented with fortified milk increase the relative abundances of Bifidobacterium spp. [ 115 ]. Probiotic supplementation with B. breve in preterm infants increases the production of serum transforming growth factor (TGF-β) levels, and enhances the deca-pentaplegic homolog3 (Smad3) mRNA expression for TGF-A signaling molecules [ 116 ].…”
Section: Short-chain Fatty Acids: a Link Between Maternal Vlckd Tmentioning
confidence: 99%
“…Intake of meats, cheeses, and Danish rye bread, rich in protein and fiber, were associated with increased alpha diversity [32]. Additionally, Matsuyama et al [33] observed significant changes in the gut microbiota community, correlated with changes in the children's dietary pattern over a period of 12 months. They noticed differential effects on specific Firmicutes-affiliated lineages in response to intake frequency of processed or unprocessed foods and positive influence of intake of fortified milk supplemented with Bifidobacterium probiotics and prebiotics (synbiotics) on Bifidobacterium spp.…”
Section: Introductionmentioning
confidence: 98%
“…They noticed differential effects on specific Firmicutes-affiliated lineages in response to intake frequency of processed or unprocessed foods and positive influence of intake of fortified milk supplemented with Bifidobacterium probiotics and prebiotics (synbiotics) on Bifidobacterium spp. [33].…”
Section: Introductionmentioning
confidence: 99%
“…All these findings make the gut microbiota an attractive target for blood pressure control, and hence various strategies are being sought to reduce blood pressure and modulate the gut microbiota. Diet could alter the gut microbiota community and influence its function by modulating the metabolites it produces [ 11 , 12 ]. Therefore, many studies have focused on the impact of different foods (high-fat diets, vegetarian diets, low-fat diets, high-fiber diets, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many studies have focused on the impact of different foods (high-fat diets, vegetarian diets, low-fat diets, high-fiber diets, etc.) on the gut microbiota [ 11 , 12 ]. Also, several other studies have developed functional foods to be used as nonpharmacological treatments for high blood pressure [ 13 ].…”
Section: Introductionmentioning
confidence: 99%